An Ir/Ni(OH)2 Heterostructured Electrocatalyst for the Oxygen Evolution Reaction: Breaking the Scaling Relation, Stabilizing Iridium(V), and Beyond. Issue 24 (4th May 2020) - Zhao, Guoqiang; Li, Peng; Cheng, Ningyan; Dou, Shi Xue; Sun, Wenping
Abstract: Developing efficient electrocatalysts for the oxygen evolution reaction (OER) is highly challenging for hydrogen production from water splitting, due to the high energy barrier for OO bond formation and the restriction of the scaling relation between the multiple reaction intermediates. In order to simultaneously address these concerns, an Ir/Ni(OH)2 heterostructure with abundant heterointerfaces is deliberately designed as an efficient electrocatalyst system, with Ir nanoparticles (NPs) homogeneously confined on the Ni(OH)2 nanosheets. The strong electronic interaction and chemical bonding across the interface between the Ir and Ni(OH)2 can effectively stabilize the metastable electrophilic Ir(V) species, which is vital to boost the formation of OO bonds. Meanwhile, the adsorption of the multiple intermediates is synergistically optimized at the heterointerface, which breaks the restrictive scaling relation and substantially accelerates the OER kinetics. In addition, the severe agglomeration of Ir species is greatly mitigated by the confinement effect, ensuring the structural integrity of the catalyst and the constant exposure of active sites. Owing to its well‐defined multifunctional interfaces, the Ir/Ni(OH)2 heterostructure exhibits exceptional OER activity and durability in alkaline media. The present results highlight the significance of heterostructure interface engineering toward the rational design and development of advanced electrocatalysts for the OER and beyond. Abstract : A highly efficient Ir/Ni(OH)2 heterostructured electrocatalyst is designed for the oxygen evolution reaction (OER). The heterointerface not only stabilizes the metastable electrophilic Ir(V) species but also breaks the scaling relation, thereby substantially promoting the OER kinetics. The results highlight the significance of heterostructure interface engineering toward the rational design of advanced electrocatalysts for the OER and beyond.